Cancer cell membrane-camouflaged MOF nanoparticles for a potent dihydroartemisinin-based hepatocellular carcinoma therapy. Issue 12 (18th February 2020) - Xiao, Yusha; Huang, Wei; Zhu, Daoming; Wang, Quanxiong; Chen, Baiyang; Liu, Zhisu; Wang, Yang; Liu, Quanyan
Abstract : Developing new drugs for cancer treatment remains a challenging task. Abstract : Developing new drugs for cancer treatment remains a challenging task. Herein, cancer cell membrane biomimetic ferrous ion-doped metal–organic framework nanoparticles (ZIF-8 nanoparticles) combined with dihydroartemisinin (DHA) have been designed for targeted cancer treatment with low toxicity and side effects. The biomimetic nanomaterials (CDZs) have excellent homologous targeting ability and can accumulate in tumor tissues. In an acid tumor microenvironment, ferrous ions and DHA could be released with the degradation of materials. DHA, an ancient Chinese medicine, combines with ferrous ions to produce a powerful anti-tumor effect. In human liver cancer models, about 90.8% of tumor growth was suppressed. In addition, the nanomaterial has no obvious toxic and side effects in vivo and is a highly effective and low-toxicity anti-tumor drug with a strong clinical application value.